IMPACT OF BANK INTERNAL FACTORS ON PROFITABILITY OF COMMERCIAL BANKS IN SRI LANKA: A PANEL DATA ANALYSIS - Jeyan Suganya, D.F.; Kengatharan, L. (University of Jaffna, 2018)
Banking system takes a major part to provide better financial services to the people in a country. Aim of this study is to examine what extent bank internal factors impact on profitability of commercial banks in Sri Lanka. Capital adequacy, Operating cost efficiency, Non-performing loans, Bank size, Liquidity, Assets Quality and Managerial efficiency are considered as bank internal factors while Return on assets is considered as profitability measure of this study. Panel data has been collected from published financial statement of nine commercial banks listed on Colombo Stock Exchange (CSE) for the period of ten years from 2006 to 2015. Fixed effect and random effect models are performed to investigate the best model to evaluate the impact of bank internal factors on profitability. Results of the study reveal that random effect model is the best model using Hausman specification test. As per the random effect model, capital adequacy has positive and significant impact on profitability while non-performing loan and operating cost efficiency have negative and significant influence on profitability. Rest of the selected variables such as bank size, liquidity, assets quality and managerial efficiency don't have any significant impact on profitability of commercial banks in Sri Lanka. The finding of this study provides information to present and future investors for making best decision on which internal factors should be well analyzed when they make investment on banking sector in Sri Lanka.
Keywords: Profitability; Capital adequacy; Operating cost efficiency; Nonperforming loans; Bank internal factors